Optimization of Thyroglobulin Coated Tube for Thyroglobulin IRMA Kit - Sutari Sutari; Triningsih Triningsih; Sri Setiyowati; V.Y. Susilo; Agus Ariyanto; Puji Widayati; Wening Lestari (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2018)
Immunoradiometric assay (IRMA) is a method of analysis based on immunological reactions of antigens-antibodies binding. This highly specific and sensitive method was used for in vitro diagnosis in small quantity of sample. Center for Radioisotope and Radiopharmaceutical Technology, BATAN has developed Thyroglobulin IRMA Kit using coated tube method that can determine thyroglobulin levels in microgram quantities. Coated tube was made with immobilisation of anti thyroglobulin into polistyrene tube. Development of IRMA kit performed through several steps including: optimization component of kit, optimization assay and kit validation. Optimization of coated tube involved selection and volume of solvent, using blocking and non-blocking agent, and volume of blocking agent. The optimum condition for coated tubes was found to be using 0.1M phosphate buffer pH 7.4 with coating volume of 500 μL, 3% BSA in 500 μL blocking agent 0.1M phosphate buffer pH 7.4, with maximum binding and non-specific binding (NSB) of 60.58 and 1.40%, respectively. The optimized coated tube was found to be stable up to 4 weeks.